Boosting the Stability of Perovskite Solar Cells through a Dopant‐Free Tetraphenylbenzidine‐Based Hole Transporting Material. Issue 46 (7th December 2018) - Xiang, Junyan; Liu, Xicheng; Sun, Mengna; Li, Xianggao; Wang, Shirong; Xiao, Yin; Zhang, Jinli; Zhang, Fei
Abstract: Developing high‐performance hole transporting materials (HTMs) is one of the hottest topics to enhance both efficiency and stability in perovskite solar cells (PSCs). One tetraphenylbenzidine (TPB) based HTM, XY1, was designed and synthesized. XY1 exhibits suitable thermal stability, film‐forming property, and hole mobility. Notably, a power conversion efficiency (PCE) of 13.23 % under 100 mW cm −2 AM 1.5G illumination is obtained from cells by using XY1 as HTM. Moreover, the unsealed device based on XY1 maintains its initial PCE for 600 h when aged under ambient air of 40% relative humidity in the dark and dropped by 30.2% after 480 h under continuous operation at 1‐sun illumination in ambient air, respectively, which is much better than devices based on Spiro‐OMeTAD. The results demonstrate a simple molecular engineering strategy to design TPB based hole‐transporting materials for highly stable perovskite solar cells, which is important for commercial application. Abstract : A low‐costTPB based HTM XY1 was synthesized and applied in PSC with a PCE of 13.23% along with outstanding stability under humidity and illumination.